化简:cos36°((sin18°)^2 -(sin72°)^2)-(sin36°)^2

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 20:19:33
化简:cos36°((sin18°)^2-(sin72°)^2)-(sin36°)^2化简:cos36°((sin18°)^2-(sin72°)^2)-(sin36°)^2化简:cos36°((sin

化简:cos36°((sin18°)^2 -(sin72°)^2)-(sin36°)^2
化简:cos36°((sin18°)^2 -(sin72°)^2)-(sin36°)^2

化简:cos36°((sin18°)^2 -(sin72°)^2)-(sin36°)^2
cos36°〔(sin18°)^2-(sin72°)^2〕-(sin36°)^2
=cos36°〔(cos72°)^2-(sin72°)^2 〕-(sin36°)^2
=cos36°(cos144°cos0°)-(sin36°)^2
=cos36°cos144°-(sin36°)^2
=cos36°(-cos36°)-(sin36°)^2
=-(cos36°)^2-(sin36°)^2
=-〔(sin36°)^2+(cos36°)^2〕
=-1